2012
DOI: 10.1074/jbc.m111.281881
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D1 Is Essential for Contraction-induced Glucose Uptake but Is Not Involved in Fatty Acid Uptake into Cardiomyocytes

Abstract: Background: Contraction of cardiomyocytes up-regulates glucose and fatty acid uptake by GLUT4 and CD36 translocation to the sarcolemma. Results: Silencing of protein kinase D1 abolishes contraction-induced GLUT4 but not CD36 translocation. Conclusion: Protein kinase D1 signaling mediates cardiac glucose but not fatty acid uptake. Significance: Selective stimulation of glucose uptake is beneficial for diabetic hearts characterized by elevated fatty acid uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 29 publications
7
64
0
Order By: Relevance
“…Interestingly, PKD has already been linked to contraction-stimulated GLUT4 translocation independent of AMPK (17). Furthermore, we recently showed that PKD selectively increased GLUT4 translocation during contraction without increasing plasmalemmal CD36 (41). Therefore, our data indicate that PKD selectively increases GLUT4 translocation through a pathway involving VAMP3.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, PKD has already been linked to contraction-stimulated GLUT4 translocation independent of AMPK (17). Furthermore, we recently showed that PKD selectively increased GLUT4 translocation during contraction without increasing plasmalemmal CD36 (41). Therefore, our data indicate that PKD selectively increases GLUT4 translocation through a pathway involving VAMP3.…”
Section: Discussionmentioning
confidence: 55%
“…However, overexpression of the contraction-regulated VAMP3 not only prevented the loss of insulin-stimulated GLUT4 translocation, but also preserved normal CD36 distribution and lipid levels during the same adverse culture conditions. Recently, we established that PKD selectively enhances GLUT4 translocation during cardiomyocyte contraction without affecting CD36 distribution or fatty acid uptake (41). The binding of VAMP3 to phosphorylated PKD could serve as an explanation of how PKD selectively targets GLUT4 translocation and how exercise improves insulin-stimulated GLUT4 translocation under conditions of impaired insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, AICAR, which in contrast to oligomycin or 4-Hz stimulation does not activate protein kinase D1, can only be used to study AMPK-mediated LCFA uptake (10). Pretreatment of cardiomyocytes with STO-609 or KN93 did not alter AMPK-Thr 172 and ACC-Ser 97 phosphorylation induced by all three AMPK-activating stimuli (Fig.…”
Section: E228mentioning
confidence: 99%
“…Whereas many signaling pathways have been shown to induce movement to the sarcolemma, to our best knowledge we are the first to show movement away. Forward transport to the sarcolemma and increased fatty acid uptake can be induced by AMPK, fatty acids, reactive oxygen species, insulin, and contraction 13,14,34,35 ; therefore, these can all be ruled out as mediating our changes in ischemia, and contraction can be ruled out at reperfusion. The location of FAT/CD36 is determined by the balance between forward movement to, and reverse movement away from, the sarcolemma 36 ; thus it could be that either pathway is affected in ischemia.…”
Section: Discussionmentioning
confidence: 99%